Case report Effectiveness of interferon α in mycosis fungoides therapy - Sikorska, Monika; Sokołowska-Wojdyło, Małgorzata; Kowalczyk, Anna; Roszkiewicz, Jadwiga (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Mycosis fungoides (MF) is the most common form of cutaneous T-cell lymphoma. Skin manifestations are generally the first signs of the disease. Many topical and systemic therapeutic alternatives are utilized in MF treatment, but there is no defined curative treatment regimen. One of the successful agents is interferon-α (IFN-α), which shows appreciable responses, especially in combination therapy with psoralen and ultraviolet A (PUVA). However, the optimal IFN dose, schedule, and duration of therapy are still not determined. We describe 2 patients suffering from MF, being treated at the Clinic of Dermatology, Venereology and Allergology in Gdansk, including IFN and phototherapy with very satisfactory results.